Why Does Deliberative Community Consultation in Large-Scale Land Acquisitions Fail? A Critical Analysis of Mozambican Experiences - Porsani, Juliana; Lalander, Rickard (Iberoamerican Journal of Development Studies, 2018)
Community consultation prior to large-scale land acquisitions (LSLA) is a cornerstone that justifies the portrayal of projects as partnerships or land grabbing. This study focuses on one of the countries most targeted by LSLA in the last decade, namely, Mozambique. The theoretical framings and everyday practices within community consultations are critically examined. The article argues that although the existence of these participatory forums is inspired by normative ideals of popular deliberation, the prevailing practices in these spaces are diametrically opposed to the theoretical foundations and values associated with deliberative democracy. As shown in this study, this mismatch between theory and practice derives largely from the interplay of hierarchical relations anchored in, inter alia, formal and customary ethnically based realms, gender disparities, and livelihood orientations. A core argument of the article is that any attempt to ameliorate these practices must consider critical insights regarding strategies to enhance social equality and inclusion in participatory spaces – challenges which are immense in places marked by deep structural inequalities.
Keywords: consultation; deliberative democracy; large-scale land acquisition; land grabbing; land rights; Mozambique